Technology commercialization: Indian university perspective - Srivastava P.; Chandra S. (My University, 2025)
Technology transfer is the complete, enabling disclosure of advancement in Science and technology, sufficient for its unfettered use and improvement. Universities and institutions of high end research and learning are the focus of such knowledge economy. University- industry partnerships in the field of Science and technology are complex and develop through a large number of mechanisms. The protection and the licensing mechanism of Intellectual property rights at such institutions are the focus of attention of the policy makers at all levels, including the Parliament, wherein a bill has been passed recently, PFIP Bill,2010, which emulates the technology commercialization at US University through Bayh Dole Act. A detailed commercialization process has been evaluated and the success of such technology transfer analysis and commercialization has been reviewed with reference to controlling parameters and revenue being generated.© Universidad Alberto Hurtado, Facultad de Economía y Negocios.